2018
DOI: 10.1002/2211-5463.12554
|View full text |Cite
|
Sign up to set email alerts
|

Wild‐type p53 regulates OTOP2 transcription through DNA loop alteration of the promoter in colorectal cancer

Abstract: Colorectal cancer ( CRC ) is the third most commonly diagnosed malignancy worldwide and remains a major public health issue. Therefore, further investigation is required to delineate the cellular and molecular mechanisms underlying colorectal tumorigenesis. Using CRC data taken from The Cancer Genome Atlas, we determined that the expression of otopetrin 2 ( OTOP 2) is highly correlated with malignancy grade and rate of patient survival. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Interestingly, several genes whose precise molecular interactions are yet to be completely understood, are among the most highly expressed genes in both proximal and distal tumors including OTOP2 (controlled by wild-type TP53) [30], OTOP3, PYY and PPIAL4; and many with limited supporting evidence, might serve as interesting candidates for future research in colon cancers ( Supplementary Table S7). Additionally, several genes discussed herein are regulated across all stages further highlighting their role in the evolution and maintenance of tumors over time, in a side-independent manner (Fig.…”
Section: A Common Program Of Tumorigenesis Exists Between Right and Lmentioning
confidence: 99%
“…Interestingly, several genes whose precise molecular interactions are yet to be completely understood, are among the most highly expressed genes in both proximal and distal tumors including OTOP2 (controlled by wild-type TP53) [30], OTOP3, PYY and PPIAL4; and many with limited supporting evidence, might serve as interesting candidates for future research in colon cancers ( Supplementary Table S7). Additionally, several genes discussed herein are regulated across all stages further highlighting their role in the evolution and maintenance of tumors over time, in a side-independent manner (Fig.…”
Section: A Common Program Of Tumorigenesis Exists Between Right and Lmentioning
confidence: 99%
“…The founding member of the OTOP family, mOTOP1, was identified as the product of a gene mutated in a murine vestibular disorder ( Hurle et al, 2003 ; Hughes et al, 2004 ) and was subsequently shown to form a proton channel that functions as a receptor for sour taste in vertebrates ( Tu et al, 2018 ; Teng et al, 2019 ; Zhang et al, 2019 ). Most vertebrate genomes encode two related proteins, OTOP2 and OTOP3, that also form proton channels ( Tu et al, 2018 ) and are expressed in a diverse array of tissues, including in the digestive tract, where mutations in the corresponding genes have been linked to disease ( Tu et al, 2018 ; Parikh et al, 2019 ; Qu et al, 2019 ; Yang et al, 2019a ). Functional OTOP channels are conserved across species, including in invertebrates, where they play roles in acid sensing and biomineralization ( Hurle et al, 2011 ; Tu et al, 2018 ; Chang et al, 2021 ; Ganguly et al, 2021 ; Mi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of CA7 was downregulated in colorectal cancer and correlated with disease progression (Yang et al, 2015 ). Proton-selective channel OTOP2 also acts a tumor suppressor gene in colorectal cancer (Qu et al, 2019 ). CFTR channel is essential for high-volume fluid secretion of water, chloride and bicarbonate in the intestine (Moran, 2017 ).…”
Section: Discussionmentioning
confidence: 99%